2022
DOI: 10.1108/jsm-04-2021-0130
|View full text |Cite
|
Sign up to set email alerts
|

Mobile payment adoption in Latin America

Abstract: Purpose Service providers have a vested interest in enhancing adoption of technologies that improve the customer service experience. Buoyed by this idea, this paper aims to explore Latin American consumers’ mobile payment (MP) adoption, conceptualized as bank-sponsored mobile wallets that facilitate payment at the point-of-purchase. This paper applies a revised unified theory of acceptance and use of technology 2 (UTAUT2) model as theoretical framework for this exploration. Design/methodology/approach To tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 77 publications
2
29
0
1
Order By: Relevance
“…Therefore, perceived usefulness influenced small businesses' intention to adopt mobile payment. Bailey et al (2022) stated that the trust level in an organization and system influenced user intention to use cellular payment. Small businesses adopted fintech due to the technology usefulness factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, perceived usefulness influenced small businesses' intention to adopt mobile payment. Bailey et al (2022) stated that the trust level in an organization and system influenced user intention to use cellular payment. Small businesses adopted fintech due to the technology usefulness factor.…”
Section: Discussionmentioning
confidence: 99%
“…The above factors influenced the intention to adopt mobile payment (Gao et al, 2018;Patel & Patel, 2018;Widyanto et al, 2021). Various research has observed the importance of security and user privacy in mobile payment (Bailey et al, 2022;Giovanis et al, 2012;Patel & Patel, 2018) defined perceived security as the extent of a person's trust in the safety of internet usage. Due to security violations such as personal data leaks and account breaches, however, small businesses need to consider security factors before adopting new technology.…”
Section: Discussionmentioning
confidence: 99%
“…loan sharks; Bustamante and Amaya, 2020; Laud et al , 2019). Although financial illiteracy remains problematic, consumers throughout the world are increasingly using digitalized financial services, namely, online banking services via mobile applications, and in locales such as Latin America (Bailey et al , 2022) and Africa (Soetan et al , 2021). Resultantly, Angus and Westbrook, (2022) suggest that a new group of consumers exist, at a global level, whom they refer to as “Financial Aficionados.” These consumers regularly use digital financial services to engage in personal money management, to take control of their money and to engage in investment opportunities.…”
Section: Digital Financial Servicesmentioning
confidence: 99%
“…This study contributes to the available literature on use of technology for mental health purposes in context of emerging Indian market for the need of mental health support. TAM since the day of its inception has been of interest for researches to understand the use of technology in various context: payment (Bailey et al, 2022), shopping (Vărzaru et al, 2021 , social media (Al-Qaysi et al, 2021 ), entertainment , food delivery (Song et al, 2021) and many more, but very few have used it to comprehend the use of mHealth apps for mental health especially in Indian setting.…”
Section: Theoretical Implicationsmentioning
confidence: 99%